ACE2 deficiency inhibits thoracic aortic dissection by enhancing SIRT3 mediated inhibition of inflammation and VSCMs phenotypic switch - Liqing Jiang; Linhe Lu; Chao Xue; He Sun; Kai Ren; Liyun Zhang; Hanzhao Zhu; Bin Zhang; Xiaoya Wang; Xinan Qiao; Xiangyan Peng; Jincheng Liu; et al. (BMC, 2024)
Abstract Background Thoracic aortic dissection (TAD) is an irreversible cardiovascular disorder with high mortality and morbidity. However, the molecular mechanisms remain elusive. Thus, identifying an effective therapeutic target to prevent TAD is especially critical. The purpose of this study is to elucidate the potential mechanism of inflammation and vascular smooth muscle cell (VSMCs) phenotypic switch in β-aminopropionitrile fumarate (BAPN)-induced TAD. Methods A mouse model of TAD induced by BAPN and IL-1β -stimulated HVSMCs in vivo and in vitro models, respectively. ACE2 Knockdown mice treated with BAPN or without, and the TAD mouse model was treated with or without AAV-ACE2. Transthoracic ultrasound was conducted for assessment the maximum internal diameter of the thoracic aorta arch. RNA sequencing analysis was performed to recapitulate transcriptome profile changes. Western blot were used to detect the expression of MMP2, MMP9, ACE2, SIRT3, OPN, SM22α and other inflammatory markers. The circulating levels of ACE2 was measured by ELISA assay. Histological changes of thoracic aorta tissues were assessed by H&E, EVG and IHC analysis. Results We found that circulating levels of and the protein levels of ACE2 were increased in the TAD mouse model and in patients with TAD. For further evidence, ACE2 deficiency decelerated the formation of TAD. However, overexpression of ACE2 aggravated BAPN-induced aortic injury and VSMCs phenotypic switch via lowered SIRT3 expression and elevated inflammatory cytokine expression. Conclusion ACE2 deficiency prevented the development of TAD by inhibiting inflammation and VSMCs phenotypic switch in a SIRT3-dependent manner, suggesting that the ACE2/SIRT3 signaling pathway played a pivotal role in the pathological process of TAD and might be a potential therapeutical target.